Regeneration, MDA, Mo carbide, zeolite, aromatic, coke - Chandra Mohan Sinnathambi (ASEAN Journal of Chemical Engineering, 2008)
Methane dehydro-aromatization (MDA) is a one-step conversion of methane to aromatics under non-oxidative condition in the presence of Mo-modified HZSM-5. The main drawback of MDA reaction is the rapid deactivation of the Mo carbide catalyst by coking. For catalyst stability and efficiency, a suitable and economical catalytic regeneration system is necessary. The present study investigates the regainability of catalyst activity by in-situ regeneration of spent 3wt% -Mo/HZSM-5 catalyst in air. Encouraging results is observed when 5% oxygen at a GHSV of 4800h-1 over 1 hour was used. The main drawback is coke is favored over aromatic product.